THE STUCTURE OF ZOOPLANKTON COMMUNITY IN MANGROVE AREA OF THE DUMAI CITY OF RIAU PROVINCE - Ardi Gunawan Siregar; Joko Samiaji; Sofyan H. Siregar (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted in August to October 2015 in the mangrove area of Dumai city of Riau Province with the aim to determine the structure of zooplankton community in form of genera and differences in the abudance of among research stations. The zooplakton sample were collected in the field and identified in the Marine Biological Laboratory of Marine Science Department, Faculty of Fisheries and Marine Sciences, University of Riau. The results showed that the zooplankton recorded consited of 8 genera i. e., Monhystera, Chromadora, Capitella, Lepadella, Monostyla, Dinizia, Mysis and Litonotus. Zooplankton average value was the highest with 936,5 ind/l and the lowest 416 ind/l. The values of diversity index (H’), dominance (D) and diversity (E) indicated that the condition of coastal waters of mangrove area of Dumai city experienced a moderate level of pollution, there was zooplankton dominance, uniformity in unbalanced so that evently not spread. Based on the calculation of the the abundance of zooplankton Anova test did not differ significantly between stations.Keyword: Coastal Waters, Dumai, Community Structure, Zooplankton